The Influence of Knowledge, Religious Beliefs, and Halal Certificate on Attitude Toward Brand, Halal Awareness and Purchase Intention: A Case Study on Safi Skincare - Khotimah, Khusnul; Mardhotillah, Rachma Rizqina (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2023)
The development of the halal cosmetics business has experienced significant growth in recent years. Halal cosmetics are beauty products that are produced and processed according to Islamic sharia principles. This includes the use of halal ingredients, without haram ingredients such as alcohol or animal ingredients that are not legislated. This study aims to analyze whether Knowledge, Religious Belief, Halal Certificate affect Attitude Toward Brand, Halal Awareness, and Purchase Intention. The population of this study is women who use or do not use Safi products. The sample of this research is 200 respondents obtained by purposive sampling. The data analysis model in this study uses path analysis with smartPLS software. The results of the study show that Knowledge, Religious Belief, Halal Certificate have a significant effect on Attitude Toward Brands, Halal Awareness, and Purchase Intention.